ANALISIS SWOT PENELITIAN DAN PENGABDIAN MASYARAKAT PUSAT PENGEMBANGAN KEWIRAUSAHAAN - Susantiningrum Susantiningrum; Eddy Triharyanto; Dimar Hantari (Universitas Sebelas Maret, 2020)
Pusat Pengembangan Kewirausahaan (PPKwu) seeks to become an independent study center, a center that has excellent activities that impact on increasing the group index through research and community service (P2M). This study aims to improve the quality and quantity of P2M so that it is expected to become an independent and superior study center. Through the preparation of a SWOT analysis, the study center is expected to improve and connect the study center services to students and the community, increase the Group Index so that it can achieve UNS's mission, UNS to become a world-class university. The preparation of SWOT analysis was carried out using the Focus Group Discussion (FGD) method. The resource persons and discussants are PPKwu peer groups. The results of this study are to obtain a SWOT analysis and a plan for improvement from the SWOT analysis. The improvement plans that have been prepared include: developing networks and cooperation for entrepreneurship development with various parties both domestically and abroad in relation to research and community service; improve the quality of Community Service in the form of education & training, consultation, apprenticeship, mentoring and research in the field of entrepreneurship; initiating the growth of WUB among students and society; conduct research related to the development of WUB and businesses that are owned by students and the community; publishing research results on entrepreneurship development through national and international journals and websites; making textbooks on entrepreneurship and entrepreneurial culture; conduct research on entrepreneurship development models; dedication of WUB and UMKM facilitation to apply for HKI.Keywords: analysis, ppkwu, study center, SWOT